Analysis Of Overtime Work, Time Management, And Job Satisfaction On Employees’ Work-Life Balance (Study At PT. Idricipta Aditama Grutty Shoes, Bags & Fashion Bandung) - Nazwa Aulia Rahmah; Aurik Gustomo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aimed to determine the effect of Overtime Work, Time Management, and Job Satisfaction on Work-Life Balance at PT Idricipta Aditama Grutty Shoes, Bags & Fashion Bandung. This research method uses descriptive and verification analysis with a quantitative approach. The source of this research uses primary data. This research data collection uses a questionnaire. The sample of this study was 144 employees at PT Idricipta Aditama Grutty Shoes, Bags & Fashion Bandung using a simple random sampling technique. Data analysis was performed with multiple regression analysis. This study's results indicate a significant influence on the work-life balance between overtime work, time management, and job satisfaction, where these variables have an effect of 89.5%. There is a negative and significant influence between Overtime Work on Employees' work-life balance, a positive and significant impact of Time management on Employees' work-life balance, and a positive and significant effect of Job satisfaction on Employees' work-life balance.